The Docosahexanoic Acid: From the Maternal-Fetal Dyad to Early Life Toward Metabolomics - Federica Comitini; Chiara Peila; Vassilios Fanos; Alessandra Coscia (Frontiers Media S.A., 2020)
Docosahexaenoic acid (DHA) is an essential ω-3 long-chain polyunsaturated fatty acid (LCPUFA) and represents the dominant structural fatty acid in the retina and in the brain's gray matter. Due to its active participation in the development of the nervous system, DHA is one of the most studied LCPUFA and is currently considered a critical nutrient during pregnancy and breastfeeding. Increasing evidence in literature suggests that an adequate concentration of DHA is required from the fetal stage through to early life to ensure optimal neurological development. Likewise, many studies in literature demonstrated that an adequate supply of DHA during pregnancy and lactation is essential to promote proper brain development in utero and in early life. Daily supplementation of DHA in newborns has potentially stronger effects compared to maternal supplementation during pregnancy. Supplementation initiated in the second year of life in children born preterm did not result in global cognitive development improvements. Preliminary findings arising from metabolomics has reported that mother's milk and infant formula supplementation of Vitamin D associated with DHA results in a higher antioxidant and protective action, with a possible positive influence on renal function and body fat on preterm infants compared to those receiving only vitamin D. Recent applications of metabolomic studies on newborns may lead to a better understanding of the metabolic process linked to early nutrition and, subsequently, to the development of targeted and personalized nutritional strategies.